2020
DOI: 10.1007/s11255-020-02440-y
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune inflammation index is a promising non-invasive marker for the prognosis of the patients with localized renal cell carcinoma

Abstract: Purpose Our aim was to evaluate the prognostic implications of a preoperative novel index, systemic immune inflammation index (SII) in patients undergoing surgery due to renal cell carcinoma. Methods A retrospective analysis of 176 patients who underwent radical nephrectomy and diagnosed with RCC was carried out. Systemic immune inflammation index, which is calculated by neutrophil x platelet/lymphocyte, and other inflammation indexes such as neutrophil/lymphocyte ratio, platelet/lymphocyte were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…No available studies were obtained from the Cochrane Library database. A total of 14 studies (11 full-text studies and 3 conference abstracts) were finally included in the present metaanalysis [9,12,13,[14][15][16][17][18][19][20][21][22][23][24]. Figure 1 shows the study selection process.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…No available studies were obtained from the Cochrane Library database. A total of 14 studies (11 full-text studies and 3 conference abstracts) were finally included in the present metaanalysis [9,12,13,[14][15][16][17][18][19][20][21][22][23][24]. Figure 1 shows the study selection process.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…The included studies were published from 2016 to 2020, with a sample size between 70 and 646 and a cut-off value of SII between 200 and 1375. Of them, six studies assessed the relationship between SII and prognosis in renal cell carcinoma (RCC) patients, [19,[22][23][24][25][26] two investigated upper tract urothelial carcinoma (UTUC), [20,27] two focused on bladder cancer (BC), [28,29] and three explored PC. [18,30,31] In terms of the research quality evaluation, the NOS score was 9 for three datasets, 8 for six datasets, 7 for one dataset, and 6 for ve datasets, demonstrating that the included articles were overall of high quality.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…De Giorgi et al suggested that SII appears superior to the NLR as a prognostic marker in mRCC patients treated with immune check-point inhibitors 26 . Furthermore, recently, a retrospective study of 176 RCC patients who underwent radical nephrectomy observed that high SII was associated with poor OS (P=0.034) 27 . SII is also associated with an increased TNM stage, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%